Finite Element Modeling of Compressive and Splitting Tensile Behavior of Plain Concrete and Steel Fiber Reinforced Concrete Cylinder Specimens - Md. Arman Chowdhury; Md. Mashfiqul Islam; Zubayer Ibna Zahid (Advances in Civil Engineering)
Plain concrete and steel fiber reinforced concrete (SFRC) cylinder specimens are modeled in the finite element (FE) platform of ANSYS 10.0 and validated with the experimental results and failure patterns. Experimental investigations are conducted to study the increase in compressive and tensile capacity of cylindrical specimens made of stone and brick concrete and SFRC. Satisfactory compressive and tensile capacity improvement is observed by adding steel fibers of 1.5% volumetric ratio. A total of 8 numbers of cylinder specimens are cast and tested in 1000 kN capacity digital universal testing machine (UTM) and also modeled in ANSYS. The enhancement of compressive strength and splitting tensile strength of SFRC specimen is achieved up to 17% and 146%, respectively, compared to respective plain concrete specimen. Results gathered from finite element analyses are validated with the experimental test results by identifying as well as optimizing the controlling parameters to make FE models. Modulus of elasticity, Poisson’s ratio, stress-strain behavior, tensile strength, density, and shear transfer coefficients for open and closed cracks are found to be the main governing parameters for successful model of plain concrete and SFRC in FE platform. After proper evaluation and logical optimization of these parameters by extensive analyses, finite element (FE) models showed a good correlation with the experimental results.